The impact of the South China Sea dispute on ASEAN Countries' Foreign Policy Toward China : A case study of the Philippines, 2013-2022 - Yao, Tingyu; Garlick, Jeremy; Přikryl, Pavel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The South China Sea (SCS) is vital for global trade, natural resources, and geopolitical stability. As China expanded its presence, regional disputes intensified, drawing in major powers. ASEAN, though not a direct claimant, plays a key role in promoting dialogue. Among ASEAN states, the Philippines stands out for its sharp policy shifts—from legal confrontation under Aquino (2013–2016) to economic engagement under Duterte (2016–2022). This thesis asks: Why did the Philippines, under similar pressures, pursue opposing China policies within a decade? Using the Foreign Policy Analysis (FPA) framework and a qualitative case study method, the research traces how leadership styles, domestic institutions, public opinion, and international dynamics shaped policy choices. It focuses on the period 2013–2022 draws on government documents, scholarly works, and media sources to support its findings.
Vedoucí práce: Jeremy Alan Garlick
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses